Analysis of the Integration of Corporate Social Responsibility and Environmental, Social, and Governance (ESG) - Jusmarni Jusmarni; Khoirun Nisa Hsb; Rahma Diana; Tanti Widia Nurdiani; Ngurah Pandji Mertua Agung Durya (LPPPIPublishing, 2025)
The purpose of this study is to analyze the integration of corporate social responsibility and environmental, social, and governance (ESG). This study employed a qualitative research method with a descriptive approach. The data sources in this study are secondary data sources. Secondary data sources were obtained from books, journals, and related sources. The research results show that the integration of corporate social responsibility and environmental, social, and governance (ESG) is an evolution in which the more qualitative, often voluntary, corporate social responsibility is transformed into a measurable, strategic, and fundamental environmental, social, and governance (ESG) framework for building sustainable businesses and attracting investors. This integration involves integrating environmental, social, and governance (ESG) metrics directly into core strategies, rather than simply as add-on programs. The goal of integrating corporate social responsibility and environmental, social, and governance (ESG) is to attract investors and funding, enhance the company's reputation and image, improve risk management, achieve operational efficiency and cost savings, and achieve long-term sustainability.